Lessons from irrigation investment experiences: cost-reducing and performance-enhancing options for Sub-Saharan Africa - Inocencio, Arlene B.; Kikuchi, M.; Merrey, Douglas J.; Tonosaki, M.; Maruyama, A.; Jong, J. de; Sally, Hilmy; Penning de Vries, Frits W.T. (International Water Management Institute, 2005)
This study aims to systematically establish whether costs of irrigation projects in SSA are truly high, determine the factors which influence costs and recommend cost-reducing options in order make irrigation investments in SSA more attractive. The study analyzes 314 irrigation projects implemented from 1967 to 2003 in 50 countries in Africa, Asia, and Latin America funded (or assisted) by the World Bank, African Development Bank and the International Fund for Agriculture Development. The sample includes "irrigation? projects, irrigation development with power generation ("irrigation with power?) projects, and irrigation component in multi-sectoral projects (MSPs). For the latter two types of project, only the cost of the irrigation component was included in the analyses. The study distinguishes projects according to purpose (ranging from purely new construction to purely rehabilitation), type of irrigation system (river diversion, reservoir-based, tank, river/groundwater-lift, and largely drainage or flood control), mode of O&M (government managed, jointly managed, farmer-managed), and major crops irrigated. All data are obtained from project completion (PCRs) and performance audit reports (PPARs) complemented with information from staff appraisal reports. Unit irrigation costs and project performance measured by economic internal rates of return are actual figures reported in PPARs or PCRs. This report examines whether the difference in unit costs in Sub-Saharan Africa compared with other regions is significant, and identifies the key determinants of unit investment costs and performance of irrigation projects. It makes three important contributions: (1) it confirms some earlier findings about irrigation projects; (2) it disproves some popularly-held notions and incorrect perceptions about unit costs and performance of irrigation projects in Sub-Saharan Africa; and (3) it provides empirical support to some existing irrigation investment policies and programs and a basis for reconsideration of others and introduction of new ones. The report presents recommendations for formulating better irrigation projects and a clear investment direction in agricultural water in Sub-Saharan Africa.